The size distribution of nanoparticles emitted from advanced manufacturing devices impacts predicted carcinogenic potential - Hill, W. Cary; Korchevskiy, Andrey (Frontiers in Public Health, 2025)
Advanced manufacturing devices such as 3D printers bring users into closer contact with processes that generate ultrafine particles or release engineered nanomaterials. While approaches to assessing the risk of lung carcinogenesis and related health effects are developing, serious questions exist regarding the impact such devices may have on human health and safety if proper actions (i.e., engineering controls including ventilation or filtration) are not taken to mitigate exposures. The size distribution of particulates emitted during fused deposition modeling (FDM) 3D printing was measured following the ANSI/CAN/UL 2904 method and associated lung cancer risk was estimated through a developing model. Particulate morphologies were assessed, identifying agglomerative and morphological characteristics which may further impact health effects. The estimation of excess lung cancer risk for 3D printer emissions based upon particle size was found to vary according to aerodynamic diameter distribution and emitted concentration, with values projected as high as 468 cases per 10,000 workers in the measured exposure scenario (1 m3 enclosure with air fully exchanged once per hour); predicted excess lung cancer risk was found to drop significantly as print extrusion temperature decreased. Actual health impacts will depend highly upon the exposure scenario, as room air volume, ventilation, and number of printers in operation will impact the concentration of particulates present. This model provides a means for assessing excess lung cancer risk across a broad aerodynamic diameter distribution, improving resolution over methods that use a single particle size bin such as PM2.5 or PM10. The effects of particle composition are only anecdotally considered in this model, however; this limitation should be accommodated as the model is implemented in practical settings.